Interactive Multimedia Based on Entrepreneurship Learning of Tandusan Oil on Needs and Economic Activities Topic - Ni Putu Martha Pebrianti; Anak Agung Gede Agung; Made Vina Arie Paramita (Journal of Education Technology, 2026)
Low learning outcomes in elementary science subjects related to “Our Needs” and economic activities indicate the limited use of interactive and contextual learning media in classroom instruction. This study aimed to develop and evaluate the feasibility and effectiveness of entrepreneurship-based interactive multimedia on minyak tandus for fourth-grade elementary school students. Research employed a research and development approach using the ADDIE model. Research subjects involved learning content experts, learning design experts, learning media experts, and fourth-grade students of SD. Data collection methods included questionnaires, observations, interviews, and multiple-choice tests. Data were analyzed using descriptive qualitative analysis, descriptive quantitative analysis, and inferential statistics through the dependent sample t-test. Validation results showed that the multimedia achieved very good qualifications from learning development design experts (93.18%), learning content experts (93.75%), learning design experts (95%), learning media experts (95%), individual trials (93.44%), and small-group trials (92.46%). Effectiveness testing demonstrated significant improvement in students’ learning outcomes, with the average score increasing from 50.67 in the pre-test to 84.33 in the post-test. Dependent sample t-test results indicated that tcount exceeded ttable (39.414 > 2.045), confirming a significant difference before and after multimedia implementation. Findings indicate that entrepreneurship-based interactive multimedia on minyak tandus is valid, feasible, and effective for improving students’ understanding, learning motivation, and entrepreneurial values.